Początek i koniec według Pawła Beręsewicza - Lewandowicz -Nosal, Grażyna (Paidia i Literatura, 2020)
The article discusses and analyzes two short stories written by Paweł Beręsewicz, Kloss and Pięć niedźwiedzi (Five bears), contained in a short story collection entitled Ściśle tajne (Top secret). The considerations pertain to death and the beginning of human life, the author’s philosophy. The said two short stories decisively have educational and cognitive value; they can serve as a stimulus to discuss existential topics with children.